Prescribing Practices of Valproic Acid for Agitation and Delirium in the Intensive Care Unit. Issue 3 (March 2021) - Quinn, Nicholas J.; Hohlfelder, Benjamin; Wanek, Matthew R.; Duggal, Abhijit; Torbic, Heather
Background: Analgesics, sedatives, and antipsychotics are commonly prescribed for agitation and delirium in the intensive care unit (ICU), but their use is limited by adverse effects and lack of efficacy. Valproic acid is an alternative treatment option. Objective: The primary objective of this study was to describe valproic acid prescribing in our institution's ICUs when used for agitation or delirium. Measures of effectiveness and safety were also assessed. Methods: This was a single-center, retrospective, institutional review board–approved cohort study of adult inpatients admitted to the ICU between January 2018 and August 2018. Patients who received valproic acid for the treatment of agitation or delirium for ≥24 hours were included. Prescribing practices were evaluated for dose, frequency, and route of administration. Effectiveness was assessed via agitation and delirium assessment tools and quantity of adjunctive agents used. Results: A total of 80 patients were included, with 35 receiving valproic acid alone and 45 in conjunction with antipsychotics. The most common valproic acid regimen was 250 mg orally 3 times daily. Delirium resolution occurred in 55% of patients: 24 in the valproic acid monotherapy group and 20 in the valproic acid plus antipsychotic group (69% vs 44%; P = 0.03). The incidence of delirium decreased from valproic acid day 0 to day 3 (93% vs 68%; P < 0.01), with no change in agitation (64% vs 63%; P = 0.28). Conclusion and Relevance: Valproic acid is frequently prescribed in agitated, delirious patients at our institution and may have a role in the management of ICU delirium.